5-(-6x-8)+5(2x-18)=3x

Simple and best practice solution for 5-(-6x-8)+5(2x-18)=3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-(-6x-8)+5(2x-18)=3x equation:


Simplifying
5 + -1(-6x + -8) + 5(2x + -18) = 3x

Reorder the terms:
5 + -1(-8 + -6x) + 5(2x + -18) = 3x
5 + (-8 * -1 + -6x * -1) + 5(2x + -18) = 3x
5 + (8 + 6x) + 5(2x + -18) = 3x

Reorder the terms:
5 + 8 + 6x + 5(-18 + 2x) = 3x
5 + 8 + 6x + (-18 * 5 + 2x * 5) = 3x
5 + 8 + 6x + (-90 + 10x) = 3x

Reorder the terms:
5 + 8 + -90 + 6x + 10x = 3x

Combine like terms: 5 + 8 = 13
13 + -90 + 6x + 10x = 3x

Combine like terms: 13 + -90 = -77
-77 + 6x + 10x = 3x

Combine like terms: 6x + 10x = 16x
-77 + 16x = 3x

Solving
-77 + 16x = 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-77 + 16x + -3x = 3x + -3x

Combine like terms: 16x + -3x = 13x
-77 + 13x = 3x + -3x

Combine like terms: 3x + -3x = 0
-77 + 13x = 0

Add '77' to each side of the equation.
-77 + 77 + 13x = 0 + 77

Combine like terms: -77 + 77 = 0
0 + 13x = 0 + 77
13x = 0 + 77

Combine like terms: 0 + 77 = 77
13x = 77

Divide each side by '13'.
x = 5.923076923

Simplifying
x = 5.923076923

See similar equations:

| 3x+6=-2x+11 | | -0.7x=0.5 | | 10x-7=4x+5 | | 6+4(5n+4)-n= | | 1045-x=729-3x | | 4x-6=-6x-4 | | 1-2y=7y+8 | | 0.83x=-1.7 | | 5-(x+2)-15=4x+23-6x | | N+7=-3 | | 0.6t+7=-8 | | x^2+8x-3=0 | | 5+3y=-1+4y | | 12m+16=2(6m+8) | | 2d-6=5 | | 8-7y=y+24 | | x^2+5x+5=0 | | 5x-91=4x-77 | | 5.5-x=1.5+2x | | x^2+4x=7 | | x^2-4x+1=0 | | 4x=5x+8 | | 7x+1=5x-7 | | x^2-7x-18=0 | | x^2+x+11=14 | | 8x^2-11x=0 | | x(x^2+8)=7+x^3 | | 5+x=-7+8x | | 13(5x-3)=9x-6 | | 5x-1=2-x | | -36=9x+18 | | 2x+10=50 |

Equations solver categories